Решите уравнение это х+1,8-0,4(9-х) = -0,3(х-9).

саня45рг саня45рг    3   14.05.2020 10:30    0

Ответы
немагистор немагистор  14.10.2020 18:06

Пошаговое объяснение:

-1,2х+1,8-3,6+0,4х=-0,3х+2,7

-0,8х-1,8=-0,3х+2,7

-0,5х=4,5

х=-9

-1,2*-9+1,8-0,4*(9-(-9))=-0,3*(-9-9)

10,8+1,8-7,2=5,4

12,6-7,2=5,4

надеюсь все понятно

ПОКАЗАТЬ ОТВЕТЫ
neketapro neketapro  14.10.2020 18:06

ответ: х=-9

Пошаговое объяснение:

На фото


Решите уравнение это х+1,8-0,4(9-х) = -0,3(х-9).
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика